Implementation of the Quizizz Application as An Alternative Media for Learning Assessment in Universities During the Covid-19 Pandemic - Asih Andriyati Mardliyah (Universitas Veteran Bangun Nusantara, 2023)
During the covid-19 pandemic, the learning process was carried out online, including at the Islamic University of Majapahit. But there are many obstacles in the implementation of online learning, such as network problems and decreased interest in learning by students. This is because learning through LMS occurs monotonously. In order for online learning to continue to be interesting, a learning innovation is needed, namely the use of quizizz aplication. The purpose of this study is to describe the use of quizizz application as an alternative media of attractive and fun assessment, especially in educational psychology courses in the pandemic covid-19 and can improve understanding of educational psychology materials.This research is a qualitative research with a case study approach. The research data was obtained through observation, interviews, and the results of the quiz assessments on the quizizz application. The results showed that the use of the quizizz application made learning more fun, increased student enthusiasm and motivation to learn and helped students understand educational psychology material.